Cellular architecture of evolving neuroinflammatory lesions and multiple sclerosis pathology - Kukanja, Petra; Langseth, Christoffer M.; Rubio Rodríguez-Kirby, Leslie A.; Agirre, Eneritz; Zheng, Chao; Raman, Amitha; Yokota, Chika; Avenel, Christophe; Tiklová, Katarina; Guerreiro-Cacais, André O.; Olsson, Tomas; Hilscher, Markus M.; et al. (Cell, 2024)
Multiple sclerosis (MS) is a neurological disease characterized by multifocal lesions and smoldering pathology. Although single-cell analyses provided insights into cytopathology, evolving cellular processes underlying MS remain poorly understood. We investigated the cellular dynamics of MS by modeling temporal and regional rates of disease progression in mouse experimental autoimmune encephalomyelitis (EAE). By performing single-cell spatial expression profiling using in situ sequencing (ISS), we annotated disease neighborhoods and found centrifugal evolution of active lesions. We demonstrated that disease-associated (DA)-glia arise independently of lesions and are dynamically induced and resolved over the disease course. Single-cell spatial mapping of human archival MS spinal cords confirmed the differential distribution of homeostatic and DA-glia, enabled deconvolution of active and inactive lesions into sub-compartments, and identified new lesion areas. By establishing a spatial resource of mouse and human MS neuropathology at a single-cell resolution, our study unveils the intricate cellular dynamics underlying MS. [Display omitted] •ISS elucidates cellular dynamics of EAE model and architecture of human MS lesions•Active EAE lesions propagate in a centrifugal manner•EAE DA-glia are induced independently of lesions and dynamically resolved•Spatial preferences of glial states drive MS lesion compartmentalization Spatial mapping of mouse and human multiple sclerosis neuropathology at a single-cell resolution unveils the cellular architecture and dynamics underlying disease evolution.